PENGEMBANGAN WEBSITE INTERAKTIF BERMUATAN KEARIFANLOKAL PROSPEKTIF PENDIDIKAN BERKELANJUTAN - Suci Trisia Maharani, - (2023)
Pengembangan website interaktif ini merupakan sumber dan media pembelajaran yang mengenalkan nilai dan jenis kearifan lokal Garut dalam konteks pendidikan yang berkelanjutan. Tujuan dalam penelitian untuk mendeskripsikan, mengidentifikasi, serta memverifikasi respon pengguna terhadap wesbite interaktif bermuatan kearifan lokal. Metode dan desain penelitian yang dikembangkan menggunakan Desain and Development (DnD) model Paffers, dkk dengan melalui tahapan: 1) identify the problem, 2) describe the objectives, 3) design and development the artifact, 4) test the artifact, 5) evaluate testing result, 6) communicate the testing results. Partisipan dalam penelitian ini adalah peserta didik kelas 4 SDIT Miftahul Huda-Garut dan guru-guru se-Kecamatan Pangatikan Garut. Hasil verifikasi dari tim ahli mendapatkan nilai 93 % dan dari respon pengguna didapatkan hasil 91,38 % dengan kategori sangat layak. Kemampuan pemecahan masalah sosial peserta didik setelah menggunakan wesbite ini mendapatkan nilai rerata 36,08. Keberterimaan sumber dan media website interaktif bagi guru sangat dipengaruhi oleh faktor facilitating condition, ICT usage habbits, dan social influences. ----- The development of this interactive website is a source and learning media that introduces the values and types of local Garut wisdom in the context of continuing education. The aim of this research isto describe, identify, and verify user responses to interactive websites containing local wisdom. The research method and design were developed using the Design and Development (DnD) model of Paffers, et al by going through the stages: 1) identify the problem, 2) describe the objectives, 3) design and develop the artifact, 4) test the artifact, 5) evaluate testing results, 6) communicate the testing results. The participants in this study were grade 4 students at SDIT Miftahul Huda-Garut and teachers from Pangatikan Garut District. The results of the verification from the expert team got a score of 93% and from the user's response the results were 91.38% with a very decent category. Students' ability to solve social problems after using this website gets an average value of 36.08. The acceptability of interactive website sources and media for teachers is strongly influenced by facilitating conditions, ICT usage habits, and social influences.